2000
DOI: 10.1067/mva.2000.105957
|View full text |Cite
|
Sign up to set email alerts
|

Effective hemodynamic diameter: An intrinsic property of vein grafts with predictive value for patency

Abstract: An EHD is a unique parameter that quantifies conduit size and has a significant impact on vein graft patency. An EHD less than 3.6 mm portends graft failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Z L was determined based on the summation of the longitudinal impedance moduli, , for each harmonic n = 1 to 8 Hz, where . This methodology is based on the vein graft patency studies by Meyerson et al [42] and Skelly et al [43] and utilized in the thesis work of Kalata [44].…”
Section: Methodsmentioning
confidence: 99%
“…Z L was determined based on the summation of the longitudinal impedance moduli, , for each harmonic n = 1 to 8 Hz, where . This methodology is based on the vein graft patency studies by Meyerson et al [42] and Skelly et al [43] and utilized in the thesis work of Kalata [44].…”
Section: Methodsmentioning
confidence: 99%
“…The zero-eth harmonic was not included as the focus of this study was on unsteady resistance. The above methodology is based on a similar calculation performed in vein graft patency studies by Meyerson, et al and Skelly, et al [29], [30]. A similar method has also been employed to understand the hemodynamic impact of proximal aortic grafts [31].…”
Section: Methodsmentioning
confidence: 99%
“…Smaller length suggests a more preserved venous segment with an optimal distal diameter. Meyerson et al [23] showed that diameter of graft smaller than 3.6 mm predicts impairment of patency and if established, a different alternative should be chosen. In a multi segmental spread of the disease, especially when the runoff arteries are partially involved, longer grafts are necessary [29], which accounts for the higher rate of the failure of bypasses with a bigger length over patent ones irrespective of their greater diameter (over 3.5 mm) by 28%.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the graft and its quality are also major determinants of the long-term success of intrainguinal reconstructions. The exact measurement of the internal venous diameter is difficult due to the different wall thickness and conical narrowing [23]. Wengerter et al [24] demonstrate a model of increasing patency in venous grafts ranging from 3.0 mm to 4.0 mm, and Idu et al [25] consider only a venous graft diameter below 3.5 mm important for the development of stenoses.…”
Section: Introductionmentioning
confidence: 99%